Climate perception and adaptability in urban/rural settlements of the Bolívar canton (Research, Society and Development, 2026)
The objective of this research is to evaluate the perception and climate adaptability of human settlements in urban and rural environments of the Bolívar canton, with the aim of generating key data that contribute to more efficient decision-making in climate change matters. An exploratory and descriptive approach was used, with a sample of 230 people distributed across the parishes of Calceta, Quiroga, and Membrillo. The research integrated climate data from the last decade (2015–2024) with surveys on perception, vulnerability, and response capacity. The climate data show variations in maximum and minimum temperatures, with significant decreases in 2020 followed by recovery, as well as marked irregularity in precipitation, with extremes of drought and intense rainfall. Regarding perception, more than 90% of respondents recognize significant impacts of climate change on their environment, highlighting alterations in rainfall patterns, loss of biodiversity, and effects on agricultural production. Furthermore, 95% identify that the temperature increase compromises water availability. In the socioeconomic sphere, 76% of participants earn less than $450, and 67% depend on agriculture, which increases their vulnerability. Urban communities demonstrate a greater capacity to respond through planning, education, and resilience projects, while rural communities rely on traditional practices such as crop diversification and seed banks. The study concludes that community resilience can be strengthened through ecosystem-based adaptation strategies, linking local initiatives with national policies.